International origins of social and political theory - Barkawi, Tarak; Lawson, George, 1972- (Political power and social theory, 2017)
This special issue is animated by the necessary entanglement of theory and history, the cortical relationship between theory and practice, and the transboundary relations that help to constitute systems of thought and practice.